3D hierarchical ACFs-based micromotors as efficient photo-Fenton-like catalysts. (March 2020) - Cui, Xinling; Li, Jia; Ng, Dickon H.L.; Liu, Jun; Liu, Yong; Yang, Wenning
Abstract: Herein, we first report a biomass route to synthesize 3D, hierarchical, ACFs (active carbon fibers)-based micromotors with superior photo-Fenton-like catalytic activity. As a biomass with unique fiber morphology, cotton fibers are abounded and inexpensive, inspiring us to explore bubble generated ACFs-based micromotors. Mn3 O4 nanosheets coated ZnO nanorods are decorated on the surface of ACFs, each component of micromotor providing different functionalities. ACFs can be an electron transfer mediator to facilitate the formation of OH radicals, adsorbent to condense organic pollutant on the surface of micromotor and support for the high dispersion of Mn3 O4 @ZnO heterojunction, facilitating the light harvesting and providing more active site. Mn3 O4 act as Fenton-like catalyst and the engine for self-propulsion. The speed of this Pt-free micromotors could reach 198 μms −1 in a 7% H2 O2 solution. It is demonstrated that fluid mixing induced by the autonomous motion significantly increases the chance of contact between reactive oxygen species and pollutant molecules and thus enhances the degradation rate of pollutant, which was 3.5 times than nonproprelling counterparts. This novel ACFs-based micromotor provides new insights into the design features of micro/nanomotors for water treatment. Graphical abstract: Image 1